2012
DOI: 10.4067/s0716-10182012000600017
|View full text |Cite
|
Sign up to set email alerts
|

Sífilis congénita: presentación como shock séptico después del período neonatal

Abstract: Congenital syphilis presenting as septic shock alter the neonatal period Clinical spectrum of congenital syphilis ranges from asymptomatic infection to fulminant sepsis. Treponema pallidum is acquired crossing the placenta from the mother to the fetus during maternal spirochetemia or through direct contact of the child with an infected lesion at delivery. We report a 27 days-old previously healthy girl diagnosed with congenital syphilis. Her mother had an unremarkable previous history, adequate obstetric care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…All studies that analyzed clinical findings in children with early CS showed some shortcoming in the management of care to the pregnant woman, especially when related to tracking, diagnosing, and providing proper treatment to the mothers as soon as possible (8,28,32) . Researches carried out in Chile, Mexico, and England exposed cases of early CS in which the mothers were only reactive to the second test applied to them or during birth (22)(23)(27)(28)32) . These women may have been infected during pregnancy and present high titer levels at the moment of birth, corresponding to an early stage of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…All studies that analyzed clinical findings in children with early CS showed some shortcoming in the management of care to the pregnant woman, especially when related to tracking, diagnosing, and providing proper treatment to the mothers as soon as possible (8,28,32) . Researches carried out in Chile, Mexico, and England exposed cases of early CS in which the mothers were only reactive to the second test applied to them or during birth (22)(23)(27)(28)32) . These women may have been infected during pregnancy and present high titer levels at the moment of birth, corresponding to an early stage of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that breast milk does not transmit syphilis from the mother to the child and that, during breastfeeding, transmission can occur only if there is syphilitic breast injury, which is very rare (18). The same criterion applies to skin-to-skin contact, since Treponema pallidum is acquired by crossing the placenta or through direct contact of the child with an infected lesion at birth (19).…”
Section: Discussionmentioning
confidence: 99%